The Influence of Financial Literacy, Financial Management, and Financial Technology on Business Performance And Sustainability of Micro, Small, and Medium Enterprises In Sumatera, Indonesia - Rika Desiyanti; Nor Azilah Husin; Rini Elvira; Sefnedi Sefnedi; Tyara Dwi Putri; Chrismondari Chrismondari (Jurnal Manajemen Universitas Bung Hatta, 2023)
Business performance and business sustainability are crucial for business owners to achieve their targets. The business performance and sustainability of micro, small, and medium enterprises (MSMEs) contribute positively to the country's economy. When compared to large companies, MSMEs employ the most people. MSMEs more significantly influence the Gross Domestic Product (GDP) growth or development. MSMEs are the backbone of a nation's economy, increasing employment possibilities. The worst issue is the decline in annual sales and potential economic headwinds brought on by dropping commodity prices. This study aims to analyze the influence of financial literacy, financial management, and financial technology on business performance and the sustainability of MSMEs in Sumatra. This study was designed using a quantitative approach and questionnaire survey of MSME owners in Sumatra, Indonesia. A simple random sampling technique is used. The data were analyzed using a structural equation model (SEM). The validity, reliability test, statistical descriptive, and multiple regression tests were conducted. Financial literacy and technology affect business performance; meanwhile, financial management does not. Furthermore, the result shows financial literacy and management affect business sustainability. Financial technology does not affect the sustainability of MSMEs.